End-stage renal disease, dialysis, kidney transplantation and their impact on CD4+ T-cell differentiation - Schaier, Matthias; Leick, Angèle; Uhlmann, Lorenz; Kälble, Florian; Morath, Christian; Eckstein, Volker; Ho, Anthony Dick; Müller-Tidow, Carsten; Meuer, Stefan; Mahnke, Karsten; Sommerer, Claudia; Zeier, Martin; et al. (Immunology, 2018)
Premature aging of both CD4+ regulatory T (Treg) and CD4+ responder-T (Tresp) cells in patients with end-stage renal disease (ESRD) is expected to affect the success of later kidney transplantation. Both T-cell populations are released from the thymus as inducible T-cell co-stimulator-positive (ICOS+) and ICOS− recent thymic emigrant (RTE) Treg/Tresp cells, which differ primarily in their proliferative capacities. In this study, we analysed the effect of ESRD and subsequent renal replacement therapies on the differentiation of ICOS+ and ICOS− RTE Treg/Tresp cells into ICOS+ CD31− or ICOS− CD31− memory Treg/Tresp cells and examined whether diverging pathways affected the suppressive activity of ICOS+ and ICOS− Treg cells in co-culture with autologous Tresp cells. Compared with healthy controls, we found an increased differentiation of ICOS+ RTE Treg/Tresp cells and ICOS− RTE Treg cells through CD31+ memory Treg/Tresp cells into CD31− memory Treg/Tresp cells in ESRD and dialysis patients. In contrast, ICOS− RTE Tresp cells showed an increased differentiation via ICOS− mature naive (MN) Tresp cells into CD31− memory Tresp cells. Thereby, the ratio of ICOS+ Treg/ICOS+ Tresp cells was not changed, whereas that of ICOS− Treg/ICOS− Tresp cells was significantly increased. This differentiation preserved the suppressive activity of both Treg populations in ESRD and partly in dialysis patients. After transplantation, the increased differentiation of ICOS+ and ICOS− RTE Tresp cells proceeded, whereas that of ICOS+ RTE Treg cells ceased and that of ICOS− RTE Treg cells switched to an increased differentiation via ICOS− MN Treg cells. Consequently, the ratios of ICOS+ Treg/ICOS+ Tresp cells and of ICOS− Treg/ICOS− Tresp cells decreased significantly, reducing the suppressive activity of Treg cells markedly. Our data reveal that an increased tolerance-inducing differentiation of ICOS+ and ICOS− Treg cells preserves the functional activity of Treg cells in ESRD patients, but this cannot be maintained during long-term renal replacement therapy.
Gesehen am 20.05.2019